Pembuatan Alat Peraga Roda Energi Guna Mempermudah Proses Pembelajaran IPA Terpadu - Yunus Agustian; Dandan Luhur Saraswati; Supardi U.S (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The Integrated Science Props Energy Wheel is used as a tool to help students understand the conversion of motion energy into electrical energy and gain knowledge about the processes of catabolism and anabolism in cellular metabolism within the human body. Additionally, this tool presents a visually engaging, challenging, and enjoyable representation of the differences between molecules and compounds, aiming to attract students to study Natural Sciences. The research objective is to determine the design and working principles of the integrated energy wheel teaching aid. The research method employed is experimental method with a descriptive approach., involving the collection of data through detailed narratives and direct observation of the object under study. The study results in the creation of the integrated science props Energy Wheel, which has dimensions of 25 cm in length, 25 cm in width, and 20 cm in height. In this Energy Wheel, the conversion of motion energy into electricity is indicated by the illumination of lights mounted on the props when the wheel is turned. The illuminated lights symbolize the bond formation between simple molecules to form complex molecules, representing an anabolism reaction. When the wheel stops turning, the lights turn off, signifying the return of complex molecules to simple molecules and the occurrence of a catabolism reaction.